Penerapan Green Architecture pada Hyatt Regency Yogyakarta sebagai Sarana Penanggulangan Perubahan Iklim - Ferenina Julia Cesa; Afif Fajar Zakariya (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Climate change challenges for environmental sustainability and development achievements in Indonesia. Yogyakarta as tourist city with high migration results dense population that affects climate change. From this issue, demands arose to build hotels, which are currently found in many places in Yogyakarta, one of which is the Hyatt Regency Yogyakarta, which received an award as the winner of the National Green Hotel Award for implementing green architecture design as a step to realize sustainable architecture. This research aims to analyze effect of green architecture concept at Hyatt Regency Yogyakarta on climate change, environment, and user comfort. This research uses qualitative methods through direct observation, searching literature studies, analyzing sustainable architecture principles according to GBCI (Green Building Council Indonesia) regulations, and drawing conclusions. The results showed that Hyatt Regency Yogyakarta successfully implemented environmentally friendly design by applying energy-saving technology that can be a guideline for a building to overcome climate problems and have a good impact on present and future environment.